THE APPLICATION OF CONCURRENT ENGINEERING METHOD SUPPORTED BY VIRTUAL PROTOTYPING BASED CAD AND CAE (CASE STUDY: INTEGRATED PASSENGER SEAT PRODUCT DESIGN AND ERGONOMICS ANALYSIS USING VIRTUAL PROTOTYPING) - Chie, Ho Hwi (Industrial and Systems Engineering Assessment Journal (INASEA), 2010)
Effective fuzzy front planning end in product development phase is very important steps toÂ achieve successful product in the market. Success in ergonomics is not only determined by theÂ design itself, but also by the time and cost incurred. Some of the contributing factors to the highÂ cost of the product are lack of ergonomics skill of designer that lead to the trial and error nature ofÂ constructing the ergonomics product. Innovation ability of designer in small medium enterprise isÂ often restricted by the fact that designer have lack knowledge of ergonomics. This difficulty can beÂ reduced significantly with the application of concurrent engineering method supported by virtualÂ prototype based CAD (computer aided design) and CAE (Computer Aided Ergonomics). We canÂ integrate ergonomics with product design optimization and anthropometric parameter for suitableÂ target market prior to production. Also we can anticipate all potential injuries caused by humanproductÂ interaction during use. Effective product planning is expected to contribute to lowerÂ production cost, to cross the innovation border, and boost up Companyâs competitive advantage.